Medication adherence in adult Chinese patients with asthma: role of illness perceptions and medication beliefs. (13th June 2022) - Cai, Qingqing; Ye, Ling; Horne, Robert; Ye, Xiaofen; Xu, Qing; Jin, Meiling; Li, Xiaoyu; Lyu, Qianzhou
Abstract: Objective: This study aimed to investigate the relationship between illness perceptions, medication beliefs, and self-reported adherence to inhaled corticosteroid (ICS) therapy in adult Chinese patients with asthma. Methods: A cross-sectional survey was conducted in the asthma outpatient clinic of Zhongshan Hospital, Fudan University (Shanghai, China) between October 2018 and September 2019. Illness perceptions, medication beliefs, and medication adherence were assessed using validated scales, specifically the Medication Adherence Report Scale for Asthma, Beliefs about Medicines Questionnaire -Specific, and the Brief Illness Perception Questionnaire. Spearman correlation and multiple logistic regression were used to determine the relationship among these factors. Results : A total of 234 patients were included in this study. Of this group, 99 (42.3%) participants were non-adherent to their ICS medication. Medication adherence correlated negatively with 'illness identity' (perceived symptom), 'emotional response' (perceived emotional effect) and concerns about medication (r=-0.16, −0.16 and −0.15, respectively, p  < 0.05). After adjusting for illness perceptions, medication beliefs and demographics, beliefs about the necessity of medication (odds ratio [OR]: 1.14, 95% confidence interval [CI]: 1.01–1.30), and emotional response to the disease (OR: 0.89, 95% CI: 0.80–0.99) were significantly associated with medication adherence in patients with asthma. Conclusion: Beliefs about the necessity of medication and emotional response to the illness have a strong influence on self-reported medication adherence in adult patients with asthma in China. Interventions targeted adherence improvement among patients with asthma may be tailored to the individual's baseline perceptions and medication beliefs, and focus on modifying inaccurate illness perceptions and medication beliefs as the main targets.